1996
DOI: 10.1021/om950967p
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Molecular Structure of the First closo-Hydrido Complexes of Osmium with Carborane Ligands:  closo-3,3-(PPh3)2-3-H-3-Cl-3,1,2-OsC2B9H11 and closo-3,3-(PPh3)2-3,3-H2-1,2-Me2-3,1,2-OsC2B9H9

Abstract: Novel 12-vertex closo-hydridometallacarboranes 3,1,2-[(PPh3)2OsHXC2B9H11] (1a,b: X = Cl, H) and 3,1,2-[(PPh3)2OsH2-1,2-Me2C2B9H9] (1c) have been synthesized via oxidative addition of K+ salts of the nido-carborane anions [nido-7,8-R2-7,8-C2B9H10]- (R = H, Me), respectively, to OsCl2(PPh3)3 and characterized by spectroscopic (NMR and IR) as well as by single-crystal X-ray diffraction studies of 1a,c.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…can be successfully substituted for [( 4 -COD)Rh(acac)] in the room-temperature synthesis of complex 67a in benzene. In this case, however, the known species [3,3-(PPh 3 ) 3 -3-Cl-3-H-3,1,2-closo-OsC 2 B 9 H 12 ] [55] was formed as a by-product in small amounts due apparently to the mild exo-nido-to-closo conversion of the starting complex 66.…”
Section: Homo-and Heterometallic Exo-closo-bimetallacarboranesmentioning
confidence: 84%
“…can be successfully substituted for [( 4 -COD)Rh(acac)] in the room-temperature synthesis of complex 67a in benzene. In this case, however, the known species [3,3-(PPh 3 ) 3 -3-Cl-3-H-3,1,2-closo-OsC 2 B 9 H 12 ] [55] was formed as a by-product in small amounts due apparently to the mild exo-nido-to-closo conversion of the starting complex 66.…”
Section: Homo-and Heterometallic Exo-closo-bimetallacarboranesmentioning
confidence: 84%
“…ELO data for cis ‐[3,3‐(CO) 2 ‐3,3‐(Cl) 2 ‐3,1,2‐ closo ‐ReC 2 B 9 H 11 ] – ( FINWIJ ), cis ‐[3,3‐(CO) 2 ‐3,3‐(SPh) 2 ‐3,1,2‐ closo ‐MoC 2 B 9 H 11 ] 2– ( TOJREP ), trans ‐[3,3‐(PPh 3 ) 2 ‐3‐H‐3‐Cl‐3,1,2‐ closo ‐OsC 2 B 9 H 11 ] ( TEXYUQ ), and trans ‐[3,3‐(PPh 3 ) 2 ‐3‐H‐3‐Cl‐3,1,2‐ closo ‐RuC 2 B 9 H 11 ] ( QEXWAS ) are presented in Table . The data for FINWIJ and TOJREP clearly demonstrate that CO has a stronger trans influence than the ligands Cl and SPh, respectively, since the cis ‐CO ligands adopt positions defined by high | θ | values.…”
Section: Resultsmentioning
confidence: 99%
“…Since little attention has been given in the literature to closo -hydrido-osmacarborane clusters and no examples with the carbons-apart { nido -7,9-C 2 B 9 } ligands were reported, a single-crystal X-ray diffraction study of 13 has been undertaken. This study confirmed the closo structure of 13 and made clear some details of its cluster geometry and the arrangement of ligands at the metal vertex.…”
Section: Resultsmentioning
confidence: 99%